Decentering Motherhood: Reentry Strategies for Women on Parole and Probation. Issue 5 (19th October 2016) - Robison, Kaitlyn J.; Hughes Miller, Michelle
Abstract : As the population of mothers under state supervision rapidly increases, it is necessary to document and analyze their experiences. This research contributes to the literature by exploring the experiences of such mothers, highlighting narratives from mothers who transitioned to a halfway house as part of their reintegration. We analyze how such mothers define good mothering and how they construct and manage their own mothering in light of their histories of drug use and criminal justice involvement, which often lead to prolonged absences from their children. The discourses of priority and presence dominate the mothers' narratives, supported by expectations from both probation/parole and the halfway house. Collectively our data suggest that mothers engage in a complex negotiation between state supervision and motherhood that reimagines the nature and practice of good mothering and adapts strategies for fulfilling state obligations.